Parental Awarness of Prose Literacy for Class 3 Elementary School in Semampiran Hamlet, Ketundan Village, Pakis District, Magelang Regency - Rahmawati, Arifa; Septiyani, Tuti; Ismail, Muhammad Ghofir; Rachmawati, Umi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this study was to determine the level of parental awareness of children'sprose literacy in Semampiran Hamlet, Ketundan Village, Pakis District, MagelangRegency. This study uses a survey methodology. The data collection technique is thequestionnaire value given by the researcher to the research subject. Based on the resultsof the data, it can be concluded that students have problems in their prose literacy. Parentsdo not fully support students in developing their literacy with the lack of storytellingmentoring activities. Children also experience limited and delayed reading activities. As aresult, students have low reading comprehension and need time to understand a story text.